Piezoelectric-Assisted Removal of a Mandibular Cementoossifying Fibroma: An Innovative Technique. (12th September 2020) - Bouguezzi, Adel; Hentati, Hajer; Chokri, Abdellatif; Sioud, Sameh; Selmi, Jamil
Abstract : Diagnosis of cementoossifying fibroma is oriented by the clinical and radiological aspects of the lesion. Histology confirms the diagnosis. Treatment is surgical with enucleation-resection depending on the lesion size or wider resection with bone reconstruction in cases of large fibromas. The use of piezoelectric bone surgery is associated with low surgical trauma, exceptional precision, and fast healing response. It also allows easy performance of complex osteotomy and reduces the necessary dimensions of mucoperiosteal dissection. The purpose of the present article was to present the advantages of piezoelectric-assisted surgical removal of a cementoosseous fibroma of the mandible and to provide a precise description of the procedure using atraumatic surgery.